(untitled) (Experimental biology, 2016)
There are presented results of studies of antioxidative and membranoprotective properties of extracts from various vegetative parts of sea-buckthorn in article. On the base of our researches we can say that extracts received from various parts of plant collected in different seasons differs from each other on antioxidative and membranoprotective properties. Experimental results have revealed, leaves and stem extracts collected in summer period showed the greatest effect. The tendency of decrease in properties of extracts to inhibit accumulation of products of lipoperoxidation and erythrocyte hemolysis, allocated of the vegetative parts of a plant collected in the autumn seasons is noted. Extracts of gemmas of a plant have shown antioxidative properties too. Antioxidant effect of plant gemma’s extract essentially lower than leave’s extract. Data under the maintenance of the general polyphenols and flavanoids in extracts from various vegetative parts of sea-buckthorn berries крушиновидной are obtained.